ТУРМАЛИН-СОДЕРЖАЩИЕ МЕТАСОМАТИТЫ УРАЛЬСКИХ ИЗУМРУДНЫХ КОПЕЙ, СРЕДНИЙ УРАЛ. СТАТЬЯ III. ТУРМАЛИН-МАРГАРИТОВЫЕ ПРОЖИЛКИ С АЛЬБИТОМ, ФЛОГОПИТОМ И ХЛОРИТОМ - Кудрявцева О.Е.; Бакшеев И.А.; Попов М.П.; Устинов В.И. (My University, 2004)
Tourmalines from tourmaline-margarite veinlets can be divided into two groups. The first one is relic from phlogopitite with the FeΣ*100%/(FeΣ+Mg), Ca*100%/(Ca+Na) ratios and flour content ranging from 13.8 to 34.6%, from 18.4 to 45.9%, and from 0.11 to 0.44 apfu, respectively. The second group includes newly formed tourmaline that is simulteneous with margarite. This can be classified as variety between the shorl-dravite endmembers with the FeΣ*100%/(FeΣ+Mg) and Ca*100%/(Ca+Na) ratios ranging from 18.7 to 41.1% and from 5.5 to 16.1%. Based on the F- contents tourmaline composition ranges from dravite to fluor-dravite (0.03-0.72 apfu F). Crystallization temperature of the tourmaline estimated from the tourmaline-biotite thermometer is 350-360°C. Tourmaline-margarite veinlets have been formed at the fF2 increasing and low values of fO2 and fCO2.
Keywords: 549.6+549.612(234.852)